2010
DOI: 10.1210/endo.151.11.9994
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on Insulin Resistance and Body Composition in Overweight and Obese Women with and without Polycystic Ovary Syndrome

Abstract: J Clin Endocrinol Metab, published October 6, 2010, 10.1210/jc.2010-0828

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
110
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(117 citation statements)
references
References 0 publications
4
110
2
1
Order By: Relevance
“…Although in those subjects who lost weight, the reduction in visceral fat was 35%. A recent study in 20 young women with PCOS using a single slice multislice CT scan also observed a 10% reduction in visceral fat after 3 months of aerobic training (12) indicating that lack of significance in the current report is likely due to our small sample size. Future studies should explore further the importance of visceral fat in reproductive function in PCOS.…”
contrasting
confidence: 72%
“…Although in those subjects who lost weight, the reduction in visceral fat was 35%. A recent study in 20 young women with PCOS using a single slice multislice CT scan also observed a 10% reduction in visceral fat after 3 months of aerobic training (12) indicating that lack of significance in the current report is likely due to our small sample size. Future studies should explore further the importance of visceral fat in reproductive function in PCOS.…”
contrasting
confidence: 72%
“…16 It seems that the lifestyle changes that combine reducing food intake for weight loss and regular exercise are a preferred treatment strategy in overweight and obese women with PCOS. 17 Despite the known benefits of a healthy lifestyle, it was interesting to note that a relatively large number of girls with PCOS and controls were not aware of the positive effects of exercise on health, which supports our hypothesis that adolescents and their parents do not have sufficient information about the benefits of physical activity, particularly, in relation to the symptomatology of PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…A ramp protocol, adapted from previous studies involving women with PCOS [5,6] was used. The VO 2max was determined by the presence of at least one of the following criteria: (i) respiratory exchange ratio (VCO 2 /VO 2 )41.1; (ii) occurrence of plateau in oxygen uptake; (iii) physical volitional exhaustion [29].…”
Section: Cardiopulmonary Exercise Testmentioning
confidence: 99%
“…Exercise is a crucial component of lifestyle intervention by promoting several benefits on body composition [2][3][4][5], cardiovascular [2][3][4]6], metabolic [3,[5][6][7][8], reproductive [9][10][11][12] and psychological [13,14] health of women with PCOS. However, the long-term adherence to exercise is a challenge [15].…”
Section: Introductionmentioning
confidence: 99%